Innovating for Transformation in First Nations Health Using Community-Based Participatory Research. (June 2018) - Kyoon-Achan, Grace; Lavoie, Josée; Avery Kinew, Kathi; Phillips-Beck, Wanda; Ibrahim, Naser; Sinclair, Stephanie; Katz, Alan
Community-based participatory research (CBPR) provides the opportunity to engage communities for sustainable change. We share a journey to transformation in our work with eight Manitoba First Nations seeking to improve the health of their communities and discuss lessons learned. The study used community-based participatory research approach for the conceptualization of the study, data collection, analysis, and knowledge translation. It was accomplished through a variety of methods, including qualitative interviews, administrative health data analyses, surveys, and case studies. Research relationships built on strong ethics and protocols to enhance mutual commitment to support community-driven transformation. Collaborative and respectful relationships are platforms for defining and strengthening community health care priorities. We further discuss how partnerships were forged to own and sustain innovations. This article contributes a blueprint for respectful CBPR. The outcome is a community-owned, widely recognized process that is sustainable while fulfilling researcher and funding obligations.